Survey of Graph Energies - Ivan Gutman; Boris Furtula (Mathematics Interdisciplinary Research, 2017)
Let graph energy is a graph--spectrum--based quantity‎, ‎introduced in the 1970s‎. ‎After a latent period of 20--30 years‎, ‎it became a popular topic of research both‎ ‎in mathematical chemistry and in ``pure'' spectral graph theory‎, ‎resulting in‎ ‎over 600 published papers‎. ‎Eventually‎, ‎scores of different graph energies have‎ ‎been conceived‎. ‎In this article we provide the basic facts on graph energies‎, ‎in particular historical and bibliographic data.‎